Conjugation-induced thermally activated delayed fluorescence: Photophysics of a carbazole-benzophenone monomer-to-tetramer molecular series - Wei, Qiang; Imbrasas, Paulius; Caldera-Cruz, Enrique; Cao, Liang; Fei, Nanan; Thomas, Heidi; Scholz, Reinhard; Lenk, Simone; Voit, Brigitte; Reineke, Sebastian; Ge, Ziyi (Journal of Physical Chemistry A, 2021)
Materials exhibiting thermally activated delayed fluorescence (TADF) have been extensively explored in the last decade. These emitters have great potential of being used in organic light-emitting diodes because they allow for high quantum efficiencies by utilizing triplet states via reverse intersystem crossing. In small molecules, this is done by spatially separating the highest occupied molecular orbital from the lowest unoccupied molecular orbital, forming an intramolecular charge-transfer (iCT) state and leading to a small energy difference between lowest excited singlet and triplet states (ΔEST). However, in polymer emitters, this is harder to achieve, and typical strategies usually include adding known TADF units as sidechains onto a polymer backbone. In a previous work, we proposed an alternative way to achieve a TADF polymer by repeating a non-TADF unit, polymerizing it via electron-donating carbazole moieties. The extended conjugation on the backbone reduced the ΔESTand allowed for an efficient TADF polymer. In this work, we present a more in-depth study of the shift from a non-TADF monomer to TADF oligomers. The monomer shows non-TADF emission, and we find the delayed emission to be of triplet-triplet annihilation origin. An iCT state is formed already in the dimer, leading to a much more efficient TADF emission. This is confirmed by an almost two-fold increase of photoluminescence quantum yield, a decrease in the delayed luminescence lifetime, and the respective spectral lineshapes of the molecules.
CRIS-Team Scopus Importer:2022-04-14